2015
DOI: 10.1016/j.jhazmat.2014.08.075
|View full text |Cite
|
Sign up to set email alerts
|

Reconnaissance of 47 antibiotics and associated microbial risks in seafood sold in the United States

Abstract: Aquaculture production has nearly tripled in the last two decades, bringing with it a significant increase in the use of antibiotics. Using liquid chromatography/tandem mass spectrometry (LC-MS/MS), the presence of 47 antibiotics was investigated in U.S. purchased shrimp, salmon, catfish, trout, tilapia, and swai originating from 11 different countries. All samples (n= 27) complied with U.S. FDA regulations and five antibiotics were detected above the limits of detection: oxytetracycline (in wild shrimp, 7.7 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(52 citation statements)
references
References 53 publications
(58 reference statements)
0
52
0
Order By: Relevance
“…40 Meat from farmed fish also frequently have antibiotic residues detected, raising the concern that practices in aquaculture also could introduce antibiotics into the human food chain. 41 …”
Section: Antibacterial Exposuresmentioning
confidence: 99%
“…40 Meat from farmed fish also frequently have antibiotic residues detected, raising the concern that practices in aquaculture also could introduce antibiotics into the human food chain. 41 …”
Section: Antibacterial Exposuresmentioning
confidence: 99%
“…Polyethylene disks, conventionally used as frits in solid phase extraction cartridges, can be also used as stirred units by simply piercing them with a metallic wire. This material is hydrophobic and it is indicated for the extraction of hydrophobic compounds [66]. The material exhibits sufficient thermal stability to allow for its mild thermal desorption in a conventional headspace vial.…”
Section: Stir Disk Extractionsmentioning
confidence: 99%
“…The analysis was carried out using a triple quadrupole LC-MS/MS with positive electrospray ionization and MRM mode. A reverse-phased C 18 column was used for the separation of the drugs, and the mobile phase consisted of HPLC-grade water with formic acid and ammonium formate (A) and a mixture 1:1 (v:v) of methanol-acetonitrile [66].…”
Section: Extraction Of Sulfonamidesmentioning
confidence: 99%
“…Although strict regulations in the United States and European Union theoretically limit the presence of antibiotic residuals in imported fish products, this is not always the case. A recent study of seafood purchased in the southwestern United States but originating from 11 different countries found that five antibiotics were routinely detectable in various sources including so‐called antibiotic‐free salmon . Of note, none of the antibiotics exceeded the federally determined MRL.…”
Section: Antibiotic Use In Aquaculturementioning
confidence: 99%